PERANAN SISTEM INFORMASI AKUNTANSI SEBAGAI ALAT KONTROL STOK BARANG MASUK DAN KELUAR ATAS PEMBELIAN DAN PENJUALAN PADA PT. JAWARA FOKUS GEMILANG - Rika Indah Pratiwi; Suhariyanti Suhariyanti; Tengku Juhri Agustan (UNIVERSITAS DHARMAWANGSA, 2023)
The role of the accounting information system within the company is to provide information appropriateand trustworthy management needs to help in decision making and as control over activities company. Thisstudy aims to determine how the role of the system accounting information as a means of controlling thestock of incoming and outgoing goods purchases and sales of the effectiveness of recording inventoryreports trading at PT. Brilliant Focus Champion. The type of data used in this research is primary andsecondary data. Data collection techniques are observation and interview. This technique is used to obtaininformation in general regarding the application of information systems in controlling the stock of goodsin and out all the way to sales. The research method used is descriptive qualitative analysis method. Thismethod is done by describing the condition of PT. Focus Champion Brilliant objectively so that thecompletion of a problem is obtained faced by the company. From the research conducted, it can be seenthat the information system Accounting plays a very important role as a means of controlling merchandiseinventory PT. Jawara Focus Gemilang, but its implementation is still not effective or inadequate becausethere are still certain parts that carry out functions and more than one task, namely there is no segregationof duties between the reception, inspection, storage and the part that removes the goods from warehouse.The accounting information system is also not fully mastered by This can be seen from the number of inputerrors in the item code.